The Differencies Addition of Cristal Sugar Ratio on Red Peanut Jam in Local North Maluku - Nursafa, Nursafa; Muhamad Saleh, Erna Rusliana; Masuku, Mustamin A. (Agrikan: Jurnal Agribisnis Perikanan, 2020)
Red peanut butter tends to be easy to make and doesn't require a lot of additional ingredients. Besides jam is a processed product that is very popular with many people, especially the mobility, because it is practical and preferred as a spread of bread for the breakfast menu. This study aims to determine the chemical and organoleptic properties of red peanut butter with the addition of different sugars. This research method uses a simple Randomized Complete Design (CRD) one factor consisting of 5 treatments and three replications so as to obtain 5x3 = 15 experimental units. The treatments consisted of 5 treatments namely adding 15% sugar (K1), adding 20% sugar (K2), adding 25% sugar (K3), adding 30% sugar (K4) and adding 35% sugar (K5) with peanut porridge 1 kg The parameters observed include chemical properties, namely water content, ash content, fat content, protein content, carbohydrate content, crude fiber and dissolved solids while for organoleptic properties include color, aroma, texture and taste. The addition of different sugars gives significantly different effects on water content, carbohydrate content, protein content, color, aroma, texture and taste. Red peanut butter is the best treatment, which is the addition of 35% sugar (K5).